(untitled) (TAMADDUN NURI JURNALI, 2025)
The article comprehensively studies the issue of artistic skill in literary criticism, analyzes its scientific and theoretical foundations. The main signs of skill are revealed using the example of the stories of the writer T. Kayipberganov.